Validity Of Contracts Based On Smart Contract Generator (A Comparative Study of Indonesia and France) - Putri Nabila sahwahita; Kaharuddin (Ajudikasi : Jurnal Ilmu Hukum, 2025)
This study examines the legal validity of contracts generated by AI-based smart contract generators from the perspective of Indonesian civil law, in comparison with French law. The background lies in the development of Society 5.0, the use of blockchain and AI in contract drafting, and the absence of specific regulations on smart contracts and generators in Indonesia. This research analyses contracts produced by smart contract generators, the legal framework governing the use of smart contract generators in contract formation in Indonesia and France, and the implications of this comparative analysis for strengthening legal certainty regarding smart contract generators in Indonesia. The study is a normative juridical research using statutory and comparative approaches, relying on primary legal materials, namely the Indonesian Civil Code, the Electronic Information and Transactions Act, the French Civil Code and AI regulations, as well as secondary materials on smart contracts, blockchain, and AI. The results show that contracts generated by such tools have the characteristics of automation, immutability, transparency, security, and decentralisation, but from a legal standpoint must still satisfy the general requirements for a valid agreement. In Indonesia, smart contracts can in principle be classified as electronic contracts insofar as they comply with Article 1320 of the French Civil Code, while the generator is viewed merely as a tool owned by the parties, with legal responsibility placed on users and a remaining regulatory gap on technical aspects. In France, smart contracts generated by AI are assessed under the general rules of contract law but are reinforced by the explicit recognition of DLT in financial law and a more developed AI supervision framework. Based on these findings, the study concludes that Indonesia needs to strengthen its national framework through explicit recognition of the contractual function of smart contracts, the adoption of technical standards and liability rules for generator providers, and the development of judicial and sectoral guidelines to ensure legal certainty and protect weaker parties.